Implementation of Basic Guidance and Counseling Services in the Merdeka Curriculum - Rahmiyati, Evi; Aziz, Melly Pusvita; Marsela, Fitra; Bahri, Syaiful (Journal of English Language and Education, 2025)
The implementation of basic guidance and counseling services is essential to support student development in line with the Merdeka Curriculum's learner-centered approach. However, discrepancies remain between policy expectations and actual school practices, particularly in planning, delivery, and media integration. This study aims to examine how BK teachers implement basic counseling services and identify the challenges they encounter. Using a descriptive qualitative method, data were collected from seven BK teachers through semi-structured interviews and documentation. The findings reveal that while teachers engage in diagnostic assessments and collaborate with school stakeholders, they face obstacles such as limited infrastructure, time constraints, and unfamiliarity with curriculum principles. Media use and large-class guidance remain inconsistent. Nevertheless, teachers attempt to overcome these barriers through adaptation, collaboration, and reflective evaluation. The study concludes that effective implementation requires ongoing support, improved facilities, and targeted training for BK teachers.